Assessment of the Psychometric Properties of the Perceived Empathic and Social Self-Efficacy Scale in Chinese Adolescents - Zhao Y; Niu J; Wang Y; Wang P (Psychology Research and Behavior Management, 2024)
Yanhua Zhao,1 Jiahui Niu,1 Yuguo Wang,1 Ping Wang2 1School of Psychology, Henan University, Jinming Campus, Kaifeng, 475001, People’s Republic of China; 2Center for Teacher Education, School of Education Sciences, Henan University, Jinming Campus, Kaifeng, 475001, People’s Republic of ChinaCorrespondence: Ping Wang, Center for Teacher Education, School of Education Sciences, Henan University, Jinming Campus, Kaifeng, 475001, People’s Republic of China, Tel +86 1833 7192 620, Fax +086 2388 1801, Email yz@vip.henu.edu.cnPurpose: There is a burgeoning interest in nurturing adolescents’ social and emotional skills, acknowledging the significant influence these abilities have on adolescents’ social development and overall well-being. The Perceived Empathic and Social Self-Efficacy Scale (PESSE) emerges as a promising tool designed to capture adolescents’ self-perceptions regarding their self-efficacy in empathic and social domains. This study seeks to investigate the psychometric properties of the Chinese Version of the Perceived Empathic and Social Self-Efficacy Scale (PESSE) by examining its factor structure, measurement invariance across gender and age groups, along with its predictive validity concerning adolescent subjective and social well-being.Participants and Methods: A sample of 512 adolescents (233 boys, 265 girls) aged 10– 16 years old (M = 12.69, SD = 1.49) from mainland China participated in this study. Confirmatory factor analysis (CFA) and multi-group CFA were employed to assess the two-factor structure and the measurement invariance of the PESSE across gender and age groups.Results: The results demonstrate that the Chinese PESSE maintains robust psychometric properties as the original version, establishing its reliability (Cronbach’s alpha for empathic self-efficacy scale was 0.82, for social self-efficacy scale was 0.85) and validity for assessing adolescents perceived empathic and social self-efficacy. Additionally, findings consistently highlight positive correlations between perceived empathic and social self-efficacy and indicators for adolescents’ subjective well-being (self-esteem, positive and negative affect, and symptoms of depression and anxiety) and social well-being (perceived peer support online prosocial behavior, school connectedness, and social relationship).Conclusion: This study supports that the PESSE is a valid and reliable instrument for assessing adolescent perceived empathic and social self-efficacy, underlining the importance of fostering empathic and social self-efficacy skills in adolescence.Keywords: the perceived empathic and social self-efficacy scale, validity, measurement invariance, adolescents, well-being